The effect of surface hydroxyl groups on the adsorption properties of nanocrystalline TiO2 films - Angela Šurca Vuk; Robi Ješe; Boris Orel; Goran Dražc (International Journal of Photoenergy)
Nanocrystalline TiO2/Brij and TiO2/Pluronic films were prepared with a view to their application in electrochromic and Grätzel cells and examination of their photocatalytic effect. The films were prepared from titanium (IV) isopropoxide with the addition of Brij 56 or Pluronic F127. Films were deposited by dip-coating, thermally treated at 500 ∘C and analysed by XRD, TEM and IR analysis. XRD and TEM analyses revealed the presence of anatase nanoparticles embedded in the amorphous phase. The presence of the latter was also confirmed by a broad high-frequency shoulder of the Ti-O stretching mode at 436 cm−1 that was found for films prepared with both kinds of surfactants. Addition of surfactants decreased the size of the particles and increased the surface roughness, and consequently in IR spectra the surface hydroxyl Ti-OH modes appear between 3800 and 3600 cm−1. IR measurements also revealed that TiO2 films with surfactants have a higher photocatalytic effect which was tested for stearic acid by following the integral intensity of C-H and C=O IR bands.